Answer:
[tex]X=\frac{Z}{2}[/tex]
It is the first statement about the relationship between points X, Y, and Z.
[tex]X=\frac{3a+2b}{Y}[/tex]
It is the second statement about the relationship between points X, Y, and Z.
Step-by-step explanation:
Given,
[tex]XY=3a+2b\quad \quad ...(i)\\ZY=6a+4b\quad \quad ...(ii)[/tex]
Now from the equation [tex](ii)[/tex],
[tex]Y=\frac{6a+4b}{Z}[/tex]
put this in the equation [tex](i),[/tex]
[tex]X\left(\frac{6a+4b}{Z}\right)=3a+2b[/tex]
[tex]\Rightarrow X=\frac{Z}{6a+4b}(3a+2b)[/tex]
[tex]\Rightarrow X=\frac{Z}{2(3a+2b)}(3a+2b)[/tex]
[tex]\Rightarrow X=\frac{Z}{2}[/tex]
It is the first statement about the relationship between points X, Y, and Z.
[tex]\because XY=3a+4b[/tex]
[tex]\Rightarrow X=\frac{3a+2b}{Y}[/tex]
It is the second statement about the relationship between points X, Y, and Z.